1997
DOI: 10.1016/s0167-4889(96)00167-x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide synthase and arginase in cells isolated from the rat gastric mucosa

Abstract: Nitric oxide (NO) synthase activity, which converts arginine to citrulline and NO, is present in homogenates of rat gastric mucosal cells. The aims of this study were to identify the form of NO synthase expressed in gastric cells isolated from fed rats, and to investigate the metabolism of arginine by suspensions of intact mucosal cells. Antibodies directed against the neuronal form of NO synthase recognised a protein of 160 kDa on immunoblots of extracts of gastric cells, and stained isolated cells of approx.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Several previous works reported that mucosecretory cells were the cell type responsible for the generation of NO in the gastric epithelium (Brown et al 1992b;Price et al 1996;Byrne et al 1997;Ichikawa et al 1998;Price and Hanson 1998). In our study, NOS protein and mRNA have also been detected in mucosecretory cells.…”
Section: Mucosecretory Cellssupporting
confidence: 78%
See 1 more Smart Citation
“…Several previous works reported that mucosecretory cells were the cell type responsible for the generation of NO in the gastric epithelium (Brown et al 1992b;Price et al 1996;Byrne et al 1997;Ichikawa et al 1998;Price and Hanson 1998). In our study, NOS protein and mRNA have also been detected in mucosecretory cells.…”
Section: Mucosecretory Cellssupporting
confidence: 78%
“…In particular, in the gastric mucosa, different studies have agreed on the high content of a calcium-dependent constitutive NOS (Whittle et al 1991) that produces NO, which is involved in maintaining mucosal integrity and regulating blood flow to the epithelium, but these studies have not agreed on the particular cell types responsible for this activity. These authors, using different techniques, have reported the production of NO by mucous (Brown et al 1992b;Price et al 1996;Byrne et al 1997;Ichikawa et al 1998;Price and Hanson 1998), chief (Fiorucci et al 1995a), or endocrine (Akiba et al 1995a;Burrell et al 1996) epithelial cell types. Furthermore, the presence of NOS has also been reported in the epithelium of the forestomach (Schmidt et al 1992) and the gastric brush cells (Kugler et al 1994) of the rat.…”
mentioning
confidence: 99%
“…Neuronal nitric oxide synthase has been detected within several different types of cells of the gastrointestinal mucosa, such as the epithelium of the rat forestomach (Schmidt et al, 1992), brush cells (Kugler et al, 1994), chief cells (Fiorucci et al, 1995), and some endocrine cells (Burrell et al, 1996) and mucosecretory cells (Brown et al, 1992;Price et al, 1996;Byrne et al, 1997;Ichikawa et al, 1998;Price and Hanson, 1998). Preliminary studies investigating eNOS immunoreactivity in the gastric mucosa agree with previous reports on eNOS immunoreactivity in the rat stomach (Price et al, 1996), indicating that although eNOS was present in blood vessels penetrating the submucosa, the specialized gastric epithelial cells were eNOS negative (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The epithelial-to-neuronal communication process is very important in many areas of the body, including the bladder (Birder, 2005) and the gastrointestinal tract, and as such, the gastric epithelium is a rich source of NO. Various specialized cells within the gastric mucosa have been found to contain nNOS, including brush cells (Kugler et al, 1994), chief cells (Fiorucci et al, 1995), and some endocrine cells (Burrell et al, 1996) and mucosecretory cells (Brown et al, 1992;Price et al, 1996;Byrne et al, 1997;Ichikawa et al, 1998;Price and Hanson, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier reports suggested the epithelial NOS activity to be more nNOS dependent than eNOS dependent, and no mucosal iNOS has been found during nonpathological conditions (5,33). Hence, we tried to selectively inhibit nNOS with the purported specific inhibitor SMTC.…”
Section: Discussionmentioning
confidence: 99%